2021
DOI: 10.1007/s00167-021-06774-7
|View full text |Cite
|
Sign up to set email alerts
|

Different rotational alignment of tibial component should be selected for varied tibial tubercle locations in total knee arthroplasty

Abstract: PurposeThe main purpose of this study was to identify how the accuracy of the tibial rotation reference axes varied in populations with different tibial tubercle locations. We hypothesized that the accuracy of the axes of tibial rotation would be affected by the changes of tibial tubercle locations. MethodsSurgical epicondylar axis (SEA), medial third of the patellar tendon (1/3MPT), medial third of the tibial tuberosity (1/3MTT), medial border of the tibial tuberosity (MTT) and Akagi line were drawn. The angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, TT-TG distance can be affected by knee rotation, which is one of the most important factors affecting PD. 1 , 5 , 14 , 20 , 28 , 40 , 44 TT-TG distance has often been questioned when evaluating TTL.…”
Section: Discussionmentioning
confidence: 99%
“…However, TT-TG distance can be affected by knee rotation, which is one of the most important factors affecting PD. 1 , 5 , 14 , 20 , 28 , 40 , 44 TT-TG distance has often been questioned when evaluating TTL.…”
Section: Discussionmentioning
confidence: 99%
“…On the tibial side, due to the inability of the surgeons to locate the SEA directly on the proximal tibial osteotomy surface, the researchers have attempted to establish optimal tibial rotational axes using appropriate intra- or extra-articular anatomical landmarks, such as the medial boundary of the tibial tuberosity [ 16 , 20 ], the medial third boundary of the tibial tuberosity [ 20 , 23 ], the anterior cortex of the tibia [ 16 ], the anterior tibial crest [ 19 , 21 ] and the tibial posterior condylar [ 23 , 25 , 26 ]. However, there is still a lack of consensus on tibial rotational alignment due to the low confidence and high individual variability of reference axes [ 13 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often impossible to identify the posterior cruciate ligament termination after proximal tibial osteotomy. In addition, it was found that the accuracy of the Akagi line differed among the female and male [ 19 , 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for persistent patellofemoral pain include lateral patellar maltracking, problems related to the extensor mechanism, and less frequently patellofemoral instability [22, 24, 30]. Contrary to the extensive research that has been conducted on the influence of femoral rotation and tibial base plate positioning on the patellofemoral joint, it seems that little attention has been paid to the tibial tuberosity trochlear groove distance (TTTG), as there are but few studies specifically investigating TTTG in TKA [15, 16, 20, 26, 34, 37]. The TTTG was first described on plain radiographs by Goutallier in 1978 as “The line between the summit of the tibial tuberosity and the bottom of the trochlea groove as seen on a radiograph taken with the knee in 30 degrees of flexion and neutral rotation”.…”
Section: Introductionmentioning
confidence: 99%